Kebijakan Kebijakan Penghapusan Piutang Macet UMKM sebagai Implementasi Konsep Good Governance - Lestari, Ni Luh Putu Sri (Jurnal Widya Publika, 2025)
President Prabowo Subianto as President of Indonesia for the period 2024 - 2029 made his latest policy by ratifying Government Regulation Number 47 of 2024 concerning the Elimination of Bad Debts for Micro, Small and Medium Enterprises. The policy is an effort to increase national economic resilience regarding the empowerment of MSMEs and provide easy access to financing for MSMEs, so that in the future it will have an impact on improving the national economy. This study uses a qualitative research method with a descriptive research type. The purpose of this study is to examine and analyze the fulfillment of the concept of good governance in the enactment of the Government Regulation on the Elimination of Bad Debts for MSMEs and the application of good governance principles in making government policies. The results of the study show that the Government Regulation on the Elimination of Bad Debts for MSMEs has met three indicators of Good Governance, namely Strategic Vision, Responsiveness, Consensus Orientation so that it is hoped that the implementation of this Government Regulation can provide benefits to the community, especially MSME actors. The application of the principle of good governance is by implementing all indicators, namely Participation; Rule Of Law; Transparency; Responsiveness; Consensus Orientation; Equity, Efficiency and Effectiveness; Accountability; Strategic Vision. By writing this article, it is expected to provide benefits for academics, society or government in the form of legal understanding and provide scientific contributions along with literature to subsequent authors related to the concept of good governance in the implementation of the PP on the Elimination of Bad Debts for MSMEs. The lack of supporting data is due to the writing material being a new policy formed by the new government. The novelty of the research focuses on the analysis of the principles of good governance in the implementation of the PP policy on the Elimination of Bad Debts for MSMEs as well as in the creation of government policies so that there is novelty in this research. Keywords: Good Governance, Public Policy, Micro, Small, and Medium Enterprises.